Non-circumferential membranous resection of the trachea for paraganglioma: A case report. (2018) - Wannaz, Laure; Roumy, Aurélien; Letovanec, Igor; Lovis, Alban; Beigelman, Catherine; Ris, Hans-Beat; Gonzalez, Michel
Highlights: Although rare, paraganglioma should be included in the differential diagnosis of an intra-thoracic membranous tracheal mass. Upfront non-circumferential surgical resection of paraganglioma may be indicated. Airway reconstruction can be performed using a latissimus dorsi flap. Extra-corporeal membrane oxygenation may be useful for tracheal repair. Abstract: Introduction: Paraganglioma is a rare neuroendocrine tumor and may sometimes be located in the membranous part of the trachea. Presentation of case: We report the case of a 52-year-old man presenting a paraganglioma just above the carina with obstructive symptoms. The patient successfully underwent a non-circumferential tracheal membranous resection, followed by latissimus dorsi muscle flap repair, under peripheral extra-corporeal membrane oxygenation (ECMO). Discussion: Complex carinal resection can be avoided for tracheal membranous tumors and replaced with non-circumferential resection and direct reconstruction with a muscle flap. In addition, ECMO support may be used for airway resection and reconstruction. Conclusion: Tracheal membranous tumors can be managed without circumferential resection or direct anastomosis.